2012
DOI: 10.1371/journal.ppat.1002544
|View full text |Cite|
|
Sign up to set email alerts
|

Early Priming Minimizes the Age-Related Immune Compromise of CD8+ T Cell Diversity and Function

Abstract: The elderly are particularly susceptible to influenza A virus infections, with increased occurrence, disease severity and reduced vaccine efficacy attributed to declining immunity. Experimentally, the age-dependent decline in influenza-specific CD8+ T cell responsiveness reflects both functional compromise and the emergence of ‘repertoire holes’ arising from the loss of low frequency clonotypes. In this study, we asked whether early priming limits the time-related attrition of immune competence. Though primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 58 publications
(96 reference statements)
6
60
2
Order By: Relevance
“…Primary IAV infection of young adult mice results in a well-characterized CD8 + T-cell immunodominance hierarchy, which shifts significantly during aging (13,22). To establish when this shift occurs, we tracked CD8 + T-cell responses to four IAV-derived epitopes following infection: D b NP 366 and D b PA 224 (immunodominant), and K b PB1 703 and D b PB1-F2 62 (subdominant), at 3, 12, and 18 mo.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary IAV infection of young adult mice results in a well-characterized CD8 + T-cell immunodominance hierarchy, which shifts significantly during aging (13,22). To establish when this shift occurs, we tracked CD8 + T-cell responses to four IAV-derived epitopes following infection: D b NP 366 and D b PA 224 (immunodominant), and K b PB1 703 and D b PB1-F2 62 (subdominant), at 3, 12, and 18 mo.…”
Section: Resultsmentioning
confidence: 99%
“…The age-related decline in naïve epitope-specific CTLps may occur stochastically, leading to an equivalent rate of loss across all epitope specificities or could reflect the differential fitness of particular CTLp sets in an aged environment. Earlier experiments demonstrated that the IAV-specific immunodominance hierarchy shifts in B6 mice, with infection of aged naïve mice resulting in substantial loss of the immunodominant D b NP 366 -specific CD8 T-cell response, a maintenance of the prominent D b PA 224 -specific response, and a relative increase in the subdominant K b PB1 703 -and D b PB1-F2 62 -specific responses (13,22). A previous study also indirectly suggested that age-related "holes" emerge in the naïve CTLp TCR repertoire, particularly for those epitope-specific sets with lower precursor frequencies (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, contraction of the murine naïve T‐cell repertoire can impair T‐cell responses to immunodominant epitopes (Yager et al ., 2008; Valkenburg et al ., 2012). Intrinsic age‐related defects in naïve T‐cell responsiveness linked to gene expression profiles and cytokine secretion have also been documented in old mice (Mirza et al ., 2011; Decman et al ., 2012; Jiang et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, DCs act as antigen-presenting cells for the efficient priming of T cells recognising endogenously-processed viral peptides. CTLs induced in this way are characterised by memory responses lasting the lifetime of the mouse [18]. Although not a suitable route for human vaccination, examination of the responses induced via this non-productive provide insight into the requirements for establishing successful vaccine-induced broadly cross-reactive memory CTLs.…”
Section: Q3mentioning
confidence: 99%